Stereoselective disposition of the enantiomers of the benzoquinolinone LY191704, a human type I 5 alpha-reductase inhibitor. Differences between rats and dogs - Farid, N A; Schreiner, K M; Coleman, N L; Van Lier, R B; Wrighton, S A (Drug metabolism and disposition, 1996)
The benzoquinolinone LY191704, a potent and selective human type I 5 alpha-reductase inhibitor, is a racemic mixture of the compounds LY300502 and LY300503. Rats were treated orally with 10, 30, or 100 mg of LY191704/kg/day for 1 month. Plasma concentrations of LY191704 increased with dose. Both the AUC and maximal concentration values were reduced at 30 and 100 mg/kg on the last day, compared with the first day of treatment. In rat plasma the ratio of LY300502 to LY300503 ranged from 1.6 to 2.0 after the first dose and from 1.6 to 2.4 after the last dose. In dogs administered the same daily oral doses of LY191704 for 1 month, the plasma ratio of LY300502 to LY300503 was essentially unity at the beginning and end of the study. After daily oral administration of LY300502 or LY300503 to rats, at 30, 100, or 300 mg/kg for 14 days, the mean dose-normalized AUC value for LY300503 was 56% of that for LY300502 after the first dose and 38% after the last dose. The rate of metabolic oxidation for LY300502 in rat liver microsomes was approximately 32% of that for LY300503, whereas no differences were observed in the metabolism of the enantiomers in dog liver microsomes. The differences observed between LY300502 and LY300503 were attributed to preferential metabolism of LY300503 in rats. The data indicated that LY300503 was subject to a greater rate of metabolism than LY300502 and induced its own metabolism in rats and that the preferential metabolism of LY300503 was species-specific.